RATIONALE FOR THE COMBINED CULTIVATOR DESIGN FOR CULTIVATING SOIL LITTERED WITH PLANT REMAINS OF ROUGH-STEMMED CROPS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
After harvesting corn, an important question is to cultivate the soil and prepare the field for sowing another crop, because after harvesting there are root and leaf residues that need to be destroyed in time and quality, earning them in the soil.  Based on the analysis of the state of the field after harvesting corn, an assessment of quantitative and qualitative indicators of surface contamination and distribution of plant residues in rows and between rows was given.  This allowed us to draw conclusions about the effective method of tillage contaminated with crop residues of coarse-stemmed crops.  Taking into account the biological, physico-mechanical and morphological features of corn residues (fibrousness, elasticity, stiffness), it was concluded that for grinding post-harvest corn residues it is necessary to use active working bodies with L-shaped knives that will cultivate the soil to a depth of 6-8 cm.  grind stems and root parts, ensure a sufficient degree of grinding, good wrapping and mixing with the soil.  However, the high energy costs of milling the soil make us look for solutions for the strip use of cutters, while ensuring continuous tillage to a given depth.  According to the conclusions of these studies, a combined cultivator is proposed, which provides passive cultivation of the row spacing with folding of plant residues that are on the surface in the row zone, milling this area with cutters 20-25 cm wide.  This combination will allow to qualitatively prepare the field with grinding of all plant residues with minimization of energy costs and traction performance of the tractor. The proposed design of the cultivator-shredder is protected by a patent of Ukraine.